Interfacial engineering of van der Waals heterostructures: impacts on the excitonic and valley properties - Brito, Caique Serati de (2024)
The study of two-dimensional (2D) materials has attracted significant attention due to their unique physical properties and potential applications in optoelectronics, spintronics, and quantum technologies. Transition metal dichalcogenides (TMDs) are a crucial class of these materials, offering exceptional electronic and optical properties, such as strong excitonic effects and valley selectivity. Additionally, the emergence of layered magnetic materials, such as CrSBr, has opened up new opportunities for exploring magnetic effects in 2D heterostructures. Combining various 2D materials through interfacial engineering enables the realization of unique properties, including superconductivity, Mott insulators, moiré effects, exciton hybridization, and single-photon emitters (SPE), providing unprecedented control over physical properties. This thesis investigates the optical properties of semiconductor TMD monolayers in van der Waals heterostructures (vdW-HS), focusing on their excitonic and valley properties. Through systematic studies of photoluminescence (PL) and magneto-PL, the research explores the impact of local and smooth strain, charge transfer, moiré patterns, and magnetic proximity effects on these properties. Our findings demonstrate the generation of SPEs in WSe2 monolayers transferred to polished borogermanate glass doped with Tb3+. The nanoroughness of the glass surface, resulting from polishing, imposes a local strain on the TMD, directly influencing SPE formation. Moreover, the substrate morphology, modified by Tb3+ doping, plays a crucial role in the hybridization between defect-localized and dark excitonic states, as evidenced by magneto-PL measurements in Voigt geometry. The impact of moiré patterns in MoSe2/WS2 heterostructures with stacking angles of 0º and 60º was studied using circularly polarized magneto-PL measurements. The obtained g-factors were very similar for both high-symmetry angles, indicating weak hybridization of the conduction bands. Additionally, PL peaks at lower energies exhibited reduced g-factors, suggesting exciton confinement due to the moiré potential. These results are consistent with the developed theoretical model, which predicts weak hybridization due to type I band alignment. The combination of MoSe2 monolayers with CrSBr, an antiferromagnetic material with in-plane magnetic ordering, revealed that the PL peaks of MoSe2 acquire linear polarization orthogonal to the anisotropic emission of CrSBr, with an enhanced effect in the ferromagnetic phase. Circularly polarized PL measurements were conducted with magnetic fields ranging from -9 to 9 T along the three principal crystal axes of CrSBr. The study revealed that the intensity variations of the MoSe2 exciton and trion peaks closely follow the behavior of CrSBr, reflecting the transition from antiferromagnetic to ferromagnetic ordering. These variations were attributed to charge transfer effects and type III band alignment. The valley Zeeman effect was also observed, with distinct g-factors for positive and negative magnetic fields, indicating asymmetric coupling for the K and K’ valleys of MoSe2 to the magnetic ordering of CrSBr. These findings highlight the complex interaction between TMD monolayers, layered magnetic materials, and their interfaces, demonstrating how interfacial engineering can be employed to modulate physical properties in 2D systems. This research contributes to the understanding of condensed matter physics and suggests pathways for integrating 2D materials into advanced quantum information and spintronic technologies.